2010
DOI: 10.3892/or_00000768
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-therapy nodal status equally affects survival of patients with oesophageal squamous cell carcinoma receiving preoperative chemoradiation

Abstract: Abstract. Patients with deeply invading (T3-T4) oesophageal cancers usually receive chemoradiotherapy with or without surgery. However, the prognostic significance of pre-therapy and post-therapy lymph node (LN) status remains unclear. We studied 195 patients who received chemoradiotherapy for deeply invading oesophageal cancers (T3-4, N0-1, M0). Of these, 105 patients underwent surgery while 90 were treated by chemoradiotherapy alone. Of the 105 surgically treated patients, overall survival was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Our data showed that the significance of pathologic metastatic LNs can also be a significant risk factor to predict the patient survival. Although some similar studies in adenocarcinoma of the esophagus were performed 22, 23, there are still few reports that support our conclusion in ESCC 24. Furthermore, we showed that the appropriate cut‐off line is between 2 and 3 metastatic LNs, and that this cut‐off line is able to distinguish between good survivors and poor survivors, as the MST was 45.1 months in patients with two or fewer metastatic LNs and 11.0 months in patients with three and more metastatic LNs (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Our data showed that the significance of pathologic metastatic LNs can also be a significant risk factor to predict the patient survival. Although some similar studies in adenocarcinoma of the esophagus were performed 22, 23, there are still few reports that support our conclusion in ESCC 24. Furthermore, we showed that the appropriate cut‐off line is between 2 and 3 metastatic LNs, and that this cut‐off line is able to distinguish between good survivors and poor survivors, as the MST was 45.1 months in patients with two or fewer metastatic LNs and 11.0 months in patients with three and more metastatic LNs (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, the risk factors for early recurrence and death might somewhat differ among studies. Pathological LN metastasis is an important prognostic factor for esophageal cancer treated with NCRT followed by surgery (5,24,25). The present multivariate analysis selected ypN2/3 as the only significant independent risk factor for early recurrence and showed that it also tended to be a risk factor for early cancer death (p=0.06).…”
Section: Discussionmentioning
confidence: 62%
“…24 Miyata et al similarly concluded that the nodal status strongly affected survival in patients of SCC treated with neoadjuvant CRT (P < 0.0001). 25 Other reports have examined the correlation between recurrence patterns and LN status. Nakagawa et al showed a close relationship between the number of LN metastases and hematogenous recurrence.…”
Section: Relationship Between the Number Of Metastatic Lns And Patienmentioning
confidence: 99%